Retos y oportunidades: teatro como estrategia de mediación pedagógica para el desarrollo de habilidades sociales - Sandoval-Poveda, Alicia; González-Rojas, Viviana; Madriz-Bermúdez, Linda (Innovaciones Educativas, 2020)
Theater can be a pedagogical mediation strategy for the development of social skills of people with autism spectrum disorder (ASD). With a research-action methodology, this premise was implemented from the State Distance University, integrating a group of young people with ASD in a three-year acting training process, with the support of a team of professionals, volunteers and the families of the young participants. The objective of this process was to improve the skills of: expression of emotions, communication, self-control and teamwork. It has been possible to observe progress in these four aspects, but in particular, various challenges have been faced that have provided opportunities for the scope of the project to expand beyond the initial objectives. The knowledge generated has expanded from the field of research to the academic and extension field, as well as to setting up the Puzzle Theater Group as an inclusive space where participants find recreational, work and personal opportunities. Currently, the main challenge of the project is the consolidation and continuity as a proposal for the development of social skills and the consolidation of the Theater Company Rompecabezas.